Ecological consequences of microplastic pollution in sub-Saharan Africa aquatic ecosystems: An implication to environmental health - Edward Moto; Miraji Hossein; Ramadhani Bakari; Alfred Said Mateso; Juma Rajabu Selemani; Salma Nkrumah; Asha Ripanda; Mwemezi J. Rwiza; Elias Charles Nyanza; Revocatus L. Machunda (HydroResearch, 2024)
Microplastic pollution (MPs) emerged as a significant environmental concern due to its persistent nature. These MPs particles endure in waters, soils, and even the atmosphere, posing potential threats to the entire ecosystem. Aquatic organisms are at risk of ingesting MPs, leading to accumulation in tissues, ultimately affecting entire food chain. This study aims to provide an overview of sources of MPs, distribution, and potential environmental impacts. MPs have been documented in various substances such as bottled water, salts, seafood, and even the air. However, the full extent of the health consequences on human exposure remains uncertain. Therefore, it is imperative that we draw public attention to the presence of these pollutants in the environment. To mitigate adverse effects of MPs, reducing plastic consumption, implementing improved waste management practices, and advocating sustainable behaviors are essential for well-being of natural ecosystems and the health human populations.